Study of strengthening and toughening treatment methods in ODS FeCrAl foil fabricated by EBPVD. (July 2014) - Sun, Y.; Chen, Y.; Lin, X.; Su, H.; He, X.
<x content-type="archive" xml:space="preserve">Abstract</x> The Fe based oxide dispersion strengthened alloy has become the preferred material for future nuclear reactor fuel cladding because of its neutron radiation stabilisation and mechanical properties caused by specific composition and microstructure at high temperature. This paper investigated the microstructure characteristics and the tensile properties at room temperature and high temperature of the as deposited test samples of Y2O3 strengthened FeCrAl alloy foils fabricated by electron beam physical vapour deposition technique, as well as the annealed state, the cold rolled/recrystallisation–annealed state and cold forged/recrystallisation–annealed state samples. The results indicated that there was a fine crystal zone near the substrate of the as deposited samples, and the rest, >95% of the sample, had obvious columnar crystal structure feature. The long axis of the columnar crystals was parallel to the normal of foil surface. Annealing technology and cold deformation (including cold rolling and cold forging technology)/recrystallisation–annealing technology have been studied to eliminate this microstructure, which goes against bearing stress, and to improve the tensile properties at high temperature. The results showed that these follow-up densification treatments studied in this paper could significantly improve the microstructure of these alloy foils. The effect of annealing could completely eliminate the rectangular pyramid grain characteristics as the strength was improved. It was observed obviously that the grain arrangement of the foil surface became more compact, and the size of the grains became smaller after cold deformation/recrystallisation–annealing. The strength at high temperature improved substantially compared with the as deposited foils.